The roles of input policies in transforming agriculture in Indonesia - Arifin, Bustanul (International Food Policy Research Institute, 2014)
Indonesian agriculture has experienced a significant structural transformation in the past four decades. The growth performance of the agricultural sector remains a moderate 4.0 percent per year in 2012, a significant increase from a 2.9 percent growth right after the global financial crisis in 2010. The performance of agricultural growth is the second lowest after the mining sector’s growth of 1.5 per-cent. Agricultural performance is obviously lower than that of the manufacturing and service sectors, achieving 5.7 percent and 8.1 percent growth, respectively. The estate crops, fisheries, and food crops sectors have contributed to agricultural growth performance, mostly because the world price of such important commodities remains high, contributing significantly to the added value of agricul-tural sectors. However, in view of the quality of growth argument, a 4.0 percent growth is simply not adequate to generate more em-ployment and alleviate poverty.